Job’s Problematic Body for Both Protagonist and Recipient - van der Zwan, Pieter (Usuteaduslik Ajakiri, 2020)
For as long as Job remains an invisible voice without an exterior body, understanding his inner experiences will remain mostly elusive as well. The body of Job is “heard” in the emotional descriptions that Job gives of his pain as he experiences it kinaesthetically. When speech and sound are, however, seen as the “shadow” of the body, and in this way echoing it in its absence, the silences, like the unconscious, are the base of this body in these descriptions. In the meantime, Job’s body remains problematic as it is, firstly, not recognised by his interlocutors for lack of empathy, secondly, not by the recipient(s) for whom it is nothing but two-dimensional words, which are often almost incomprehensible due to cultural and temporal distance, and, thirdly, not even by Job himself who struggles to see in it the reality which God eventually points out to him. Yet a bridge can be built thanks to a “universal” body shared by all parties.